Population dynamics and biological aspects of Tetranychus urticae on three squash (Cucurbita pepo) varieties - RASHA, RASHA; ELHALAWANY, A S; EL-SHAHAWI, GAMAL; R, MAHMOUD M F; EL-MALLAH, AL-MAHY; ZAKI, A Y (The Indian Journal of Agricultural Sciences, 2021)
Squash (Cucurbita pepo L.) is a popular plant in Egypt, field study was carried out to evaluate the susceptibility of three squash varieties, i.e. Eskandarani, Hytech and Miletto infestation with two spotted spider mite Tetranychus urticae. Temperature and humidity played a strong role in the T. urticae infestation on squash varieties where there is a positive relationship between the population of T. urticae and temperature while negative between the population and humidity. Also, temperature plays an important role on biology of T. urticae where they completed their development and reproduced at all tested temperatures (20, 25, 30ÂºC).Also developmental time, oviposition period, adult longevity and life span decreased with increasing temperatures, while daily oviposition rate and fecundity increased with increasing temperatures. Therefore 30 ºC is the ideal degree in which all stages of growth are shortened. On the other hand the susceptibility of squash varieties to the T. urticae infestation attributable to phytochemical contents which varied from variety to another, and affect mite density levels. A positive relationship was found between mite infestations and squash leaf contents i. e. total carbohydrates, total protein and total lipids in squash leaves, while a negative one found with alkaloids and total phenolic compounds, total flavonoids and total carotenoids and chlorophyll (a&b).Thus temperature and humidity and phytochemical contents of plant leaves has an important effect on infesting squash by T. urticae.